121k views
9 votes
Find the solution of the system of equations.
−x−3y= −3
x−6y= −24

User John Owen
by
5.0k points

2 Answers

7 votes

To find the solution of the given system of equations, we can use the method of substitution or elimination. Let's use the method of substitution. The solution to the given system of equations is x = -18 and y = 7.

To find the solution of the given system of equations, we can use the method of substitution or elimination. Let's use the method of substitution:

From the first equation -x - 3y = -3, we can solve for x in terms of y: x = -3 + 3y.

Substitute this expression for x in the second equation x - 6y = -24:

-3 + 3y - 6y = -24.

Simplify and solve for y:

-3y - 3 = -24.

-3y = -21.

y = -21 / -3 = 7.

Now substitute this value of y back into the first equation to solve for x:

-x - 3(7) = -3.

-x - 21 = -3.

-x = 18.

x = -18.

Therefore, the solution to the given system of equations is x = -18 and y = 7.

User Entropo
by
5.0k points
8 votes

Answer:

(-6 , 3)

Explanation:

-x-3y= -3

x-6y= -24

1. solve each eq so they make x=___

-x = -3 + 3y

x= 3 - 3y

and

x = -24 + 6y

2. set = to each other and solve for y

3 - 3y = -24 + 6y

27 = 9y

y = 3

3. plug the y value into one of the x=__ eq's and solve for x

x = 3 - 3y

x = 3 - 3(3)

x = 3 - 9

x = - 6

your solution is ( -6 , 3 )

User Johndave Decano
by
4.2k points